RETRACTED An Agile Software Engineering Method to Design Blockchain Applications - Erliyani, Ita; wulandari, siti afifah (Blockchain Frontier Technology, 2022)
Cryptocurrencies and its underlying technology, Blockchain, are transforming banking and economics by allowing trustworthy programs to exist without the requirement for a trusted counterpart. In recent years, the Blockchain and the programs that run on it, known as Smart Contracts, have seen increased use across all businesses that demand trust and verifiable credentials. Some have compared the "Blockchain revolution" to the early days of the Internet and the World Wide Web. As a result, all Blockchain-based software development is accelerating at a dizzying pace. Many software engineers argue that the widespread interest in Blockchain technology has resulted in haphazard and rushed software creation, a type of first-come, first-served competition that fails to assure software quality or take into consideration core software engineering ideas. This research tries to solve this issue by proposing a software development strategy for gathering requirements, assessing them, designing, creating, testing, and deploying Blockchain applications. Several Agile approaches are employed in the process, including User Stories and iterative and incremental development based on them. It does, however, employ more formal notations, such as UML diagrams that define the system's design, with improvements to express unique Blockchain concepts. The method is well discussed, including an example to illustrate how it works.